Who makes a good leader? Social preferences and leading-by-example - Simon Gächter; Daniele Nosenzo; Elke Renner; Martin Sefton (Institute for the Study of Labor (IZA), 2008)
We examine the effects of social preferences and beliefs about the social preferences of others in a simple leader-follower voluntary contributions game. We find that groups perform best when led by those who are reciprocally oriented. Part of the effect can be explained by a false consensus effect: selfish players tend to think it more likely that they are matched with another selfish player and reciprocators tend to think it more likely that they are matched with another reciprocator. Thus, reciprocators contribute more as leaders partly because they are more optimistic than selfish players about the reciprocal responses of followers. However, even after controlling for beliefs we find that reciprocally-oriented leaders contribute more than selfish leaders. Thus, we conclude that differing leader contributions by differing types of leader must in large part reflect social motivations.
urn:nbn:de:101:1-20090119104
Keywords: A13; C92; D03; 330; Reciprocity; contribution preferences; leadership; leading-by-example; false consensus effect; Führungstheorie; Austauschtheorie (Soziologie); Spieltheorie